Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1935
DOI: 10.1152/ajplegacy.1935.113.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Area and the Intensity-Time Relation in the Peripheral Retina

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
4

Year Published

1940
1940
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(76 citation statements)
references
References 0 publications
5
67
0
4
Order By: Relevance
“…Below critical duration the same visual effect may be produced for the absolute threshold (4,8), differential threshold (6), grating acuity (5, 15), and span of attention (10) provided the product of intensity and time (i.e., the total energy) remains constant. This reciprocal relation, the Bunsen-Roscoe law, means for the indicated visual measures reduction of exposure time is equivalent, below critical duration, to reduction of luminance.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Below critical duration the same visual effect may be produced for the absolute threshold (4,8), differential threshold (6), grating acuity (5, 15), and span of attention (10) provided the product of intensity and time (i.e., the total energy) remains constant. This reciprocal relation, the Bunsen-Roscoe law, means for the indicated visual measures reduction of exposure time is equivalent, below critical duration, to reduction of luminance.…”
Section: Discussionmentioning
confidence: 88%
“…These functions increase rapidly at first, and then more slowly, before approaching a limiting value. 4. The diminution of the tendency toward perceptual constancy resulting from 'reduction of luminance is attributed to the impairment of visual acuity and intensity discrimination for the "additional" stimuli in the visual field.…”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69][70][71][72][73][74] In contrast, for foveal cone vision, Riccò's area holds only up to between 2-8 min of arc 72,75,76 and does not seem to change much with light adaptation (see Chen et al 77 ). Likewise, depending upon stimulus configuration and retinal eccentricity, Bloch's Law of total temporal summation is valid up to 200-270 ms for fully dark-adapted peripheral rod vision, decreasing with light adaptation to ϳ100 ms. 68,72,[78][79][80][81][82][83] In contrast, for dark-adapted foveal cone vision, Bloch's Law holds up to ϳ100 ms, decreasing with light adaptation to 30-60 ms. 68,81,[83][84][85][86] Larger spatial and longer temporal summation for rod vision will result in severe low-pass filtering of the input signal, both in the temporal and in the spatial domain. This will reduce the responses of EMD's with a short distance and a short time delay between their two receptive fields or, equivalently, EMD's highly sensitive to high spatial and high temporal frequencies.…”
Section: A Comparison With Isoluminant Stimulimentioning
confidence: 99%
“…This is in notable contrast to brightness perception. Barlow (1958) and Graham and Margaria (1935), for example, found that temporal integration has a longer duration when the stimulus area is small than when it is large. In other words, the critical duration of temporal integration increases with decreasing stimulus area.…”
Section: Separation In MMmentioning
confidence: 99%